Cushing's syndrome: from physiological principles to diagnosis and clinical care. (5th January 2015) - Raff, Hershel; Carroll, Ty
<x xml:space="preserve">Abstract</x> Abstract The physiological control of cortisol synthesis in the adrenal cortex involves stimulation of adrenocorticotrophic hormone (ACTH) by hypothalamic corticotrophin‐releasing hormone (CRH) and then stimulation of the adrenal by ACTH. The control loop of the hypothalamic–pituitary–adrenal (HPA) axis is closed by negative feedback of cortisol on the hypothalamus and pituitary. Understanding this system is required to master the diagnosis, differential diagnosis and treatment of endogenous hypercortisolism – Cushing's syndrome. Endogenous Cushing's syndrome is caused either by excess ACTH secretion or by autonomous cortisol release from the adrenal cortex. Diagnosis of cortisol excess exploits three physiological principles: failure to achieve the normal nadir in the cortisol diurnal rhythm, loss of sensitivity of ACTH‐secreting tumours to cortisol negative feedback, and increased excretion of free cortisol in the urine. Differentiating a pituitary source of excess ACTH (Cushing's disease) from an ectopic source is accomplished by imaging the pituitary and sampling for ACTH in the venous drainage of the pituitary. With surgical removal of ACTH or cortisol‐secreting tumours, secondary adrenal insufficiency ensues because of the prior suppression of the HPA axis by glucocorticoid negative feedback. Medical therapy is targeted to the anatomical location of the dysregulated component of the HPA axis. Future research will focus on new diagnostics and treatments of Cushing's syndrome. These are elegant examples of translational research: understanding basic physiology informs the development of new approaches to diagnosis and treatment. Appreciating pathophysiology generates new areas for inquiry of basic physiological and biochemical mechanisms.